Nuskha-yi khaṭṭī wa fihristnigāri-yi ān dar Īrān : Majmūʿa-yi maqālāt wa justārhā bih pās-i zaḥamāt-i sī sāla-yi Francis Richard, nuskhashinās-i bargusta-yi Faransawī, daftar-i yakum - Rīsa, Aḥmad-Riḍā Raḥīmī (Miras Maktoob, ISBN: 9789004365452., 2019)
Islamic studies are for a large part based on texts that were originally transmitted in manuscript. Even if many of these works are now available in print, improved editions are often needed, while most of the surviving texts have never been published at all. The preservation, description, and proper cataloging of Islamic manuscripts all have a direct influence on the possibility for Islamic studies to move forward and develop. For many years, Francis Richard (b. 1948) was responsible for the Persian manuscripts at the Bibliothèque Nationale de France. Author of numerous publications on Persian manuscripts and their tradition, his Splendeurs persanes, manuscrits du XIIe au XVIIe siècles (BnF, 1997) was also published in Persian in 2005. In recognition of the great services that he has rendered to Persian studies, the present work is the first of a two-volume liber amicorum by a number of distinguished Iranian scholars. Includes an inventory of the publications of Francis Richard.